Non-Pharmacological Management of Nausea and Vomiting in Cancer: A Scoping Review - Santi Wahyuningsih; Yati Afiyanti; Agung Waluyo; Margaret I Fitch (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
Prevention and management of nausea and vomiting are important in cancer treatment. Effective management requires both pharmacological and non-pharmacological interventions. Patients and family members have important contributions to achieve effective control of nausea and vomiting through self-management. The objective of this review is to explore and synthesize the scientific literature about self-management strategies as a type of non-pharmacological intervention for managing nausea and vomiting in cancer patients. The articles were searched in PubMed, Science Direct and ClinicalKey databases using keyword combinations of